ADAPTING DA'WAH COMMUNICATION STRATEGIES FOR TRADITIONAL SOCIETY - Muklisin, Muklisin; Ismail, M. Syukri; Hidayat, Anshori; Debit, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Technological advances and rapid social changes affect the way da'wah is delivered in the midst of modern society. Every institution and individual plays an important role in spreading the teachings of Islam through an adaptive approach. This research aims to explore the da'wah communication strategies applied by Muslim institutions to the local community, especially in facing the challenges of modernization and globalization. The research method used is a qualitative approach with a field study type, allowing in-depth data collection through observation, interviews, and documentation which are then analyzed using Miles and Huberman. The results of the study show that the role of local leaders as effective mediators of da'wah is due to their social authority that is recognized and respected by the community. Second, the alignment of Islamic values with existing social norms helps reduce value conflicts and increase acceptance of da'wah. Third, the use of social media allows for a wider and interactive dissemination of da'wah, reaching a younger and more diverse audience. The findings are expected to contribute to da'wah literature by providing insights into how communication strategies can be adapted to local social and cultural contexts to increase the effectiveness of da'wah in the digital era.